Liquid B2O3 up to 1700 K: x-ray diffraction and boroxol ring dissolution. (29th October 2015) - Alderman, O L G; Ferlat, G; Baroni, A; Salanne, M; Micoulaut, M; Benmore, C J; Lin, A; Tamalonis, A; Weber, J K R
Abstract: Using high energy x-ray diffraction, the structure factors of glassy and molten B2 O3 were measured with high signal-to-noise, up to a temperature of T   =  1710(20) K. The observed systematic changes with T are shown to be consistent with the dissolution of hexagonal [B3 O6 ] boroxol rings, which are abundant in the glass, whilst the high- T (⪆1500 K) liquid can be more closely described as a random network structure based on [BO3 ] triangular building blocks. We therefore argue that diffraction data are in fact qualitatively sensitive to the presence of small rings, and support the existence of a continuous structural transition in molten B2 O3, for which the temperature evolution of the 808 cm −1 Raman scattering band (boroxol breathing mode) has long stood as the most emphatic evidence. Our conclusions are supported by both first-principles and polarizable ion model molecular dynamics simulations which are capable of giving good account of the experimental data, so long as steps are taken to ensure a ring fraction similar to that expected from Raman spectroscopy. The mean thermal expansion of the B-O bond has been measured directly to be α BO   =  3.7(2)  ×  10 −6 K −1, which accounts for a few percent of the bulk expansion just above the glass transition temperature, but accounts for greater than one third of the bulk expansion at temperatures in excess of 1673 K.